2018
DOI: 10.4236/sgre.2018.912017
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isothermal Degradation and Thermodynamic Properties of Pine Sawdust

Abstract: The study of non-isothermal kinetics analyzed the reactivity of pine sawdust, while the thermodynamic properties analyzed energy consumed and released from the pine sawdust. The kinetic parameters were determined by analyzing mass loss of pine sawdust components by using Thermogravimeric analyzer. The cellulose has the highest conversion rate of 9.5%/min at 610 K compared to hemicellulose and lignin, which are 5%/min at 600 K and 2%/min at 800 K, respectively. The activation Energy for cellulose, hemicellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Generally, the presence of a higher percentage of atomic oxygen (O) compared to that of atomic carbon (C) in the biomass causes a lower heating energy, since the C–C bond is considered as the main heat source . Chaula et al showed that the ratios of O/C and H/C are directly related to the heating energy of a solid fuel, in which the presence of oxygen caused a low heating value. The proximate compositions of the biomass residue are generally fixed carbon, ash content, moisture content, and volatile matter.…”
Section: Microalgae Biomass and Its Compositionmentioning
confidence: 99%
“…Generally, the presence of a higher percentage of atomic oxygen (O) compared to that of atomic carbon (C) in the biomass causes a lower heating energy, since the C–C bond is considered as the main heat source . Chaula et al showed that the ratios of O/C and H/C are directly related to the heating energy of a solid fuel, in which the presence of oxygen caused a low heating value. The proximate compositions of the biomass residue are generally fixed carbon, ash content, moisture content, and volatile matter.…”
Section: Microalgae Biomass and Its Compositionmentioning
confidence: 99%